Ta‘Ṡīru Aṭ Ṭarīqati At Tamṡīliyyati Fi Taḥsīni Mahārati Al Kalāmi Lada Ṭullābu Al Faṣli Alḥādi Asyar Fī Al Madrasati At Tarbiyyati Al Islāmiyyati Qatū Tawa Kūmfūlān Bāsāmān Syarqiyyah - Safitri, Weniza; Yati, Yati; Zubaidah, Zubaidah; Miza, Zikra Wahyuni (DAS Institute, 2022)
The problem in this discussion is the effect of the representative method of learning Arabic on the speaking skill of students. It can be demonstrated by the value of students who exceed KKM. And to know how to speak Arabic correctly. The method I use in processing this data is the experimental quantitative method. The data is collected using observation, observations and tests, then the data collected through tests, then quantitative analysis. With this we can draw conclusions whether the method used is effective in speaking skill. The representative method makes it easier for the eleventh class students in Madrasah Tarbiyah Islamiyah Koto Tuo Kumpulan, to improve the students' speaking skills. As evidenced by the scores of students who passed KKM in the experimental class, which includes: Among the 25 students studied in this study, an average Arabic learning score of 80,58 was obtained. The highest stair in the experimental class was 92, out of 12 students, 10 scored above the kilometer and two people below the KKM. From this table, the t-test refers to the result (5,518). As for the result of t-table 2,718 in 1%, and 1,796 in bike 5%, the result of calculation t is greater than t-table. The researcher concluded that the H0 is rejected and the Ha is accepted.